Resistance Againts Patriarchal Cultural Hegemony on Instagram @laviaminora - Karunia, Risma Mei; Teguh Priyo Sadono; Hamim (Journal of Social Interactions and Humanities, 2024)
This research constitutes a qualitative descriptive analysis using Roland Barthes' semiotic theory, focusing on the concepts of denotation and connotation. Centered around the Instagram account @laviaminora, the study describes and analyzes messages of resistance against patriarchal hegemony manifested in visual texts. Employing semiotic analysis methods, this research highlights how signs of sexuality in the account serve as a form of critique against sexual repression and societal norms in Indonesia.Research findings indicate that the sexuality represented in @laviaminora is not merely a denotation of reality but also carries connotations that create subjective and emotional meanings. The account successfully constructs a narrative of resistance against longstanding myths related to patriarchal culture, emphasizing the values of women's freedom. In the context of Indonesian patriarchal society, the socio-cultural construction of sexuality is identified as a tool to maintain male dominance over women.The research concludes that @laviaminora creatively utilizes semiotics as a means to critique and resist patriarchal norms that continue to influence social and cultural life in Indonesia.